Spelling recovery - Roberts, Jan (Australian Council for Educational Research, 2001)
In every classroom there are students with different spelling abilities. As an educator, you need to be aware of the causes of spelling problems, and what appropriate action can be taken to help these students. Janet Roberts has drawn from her depth of knowledge and understanding of the current learning theories, specifically the development of spelling, to produce this invaluable teacher resource which redresses the problem of inaccurate spelling by students, empowering them to become competent spellers. Guidelines have been provided for teachers, enabling them to analyse errors in spelling and counter them with specific and direct teaching methods. It is not only important to identify the skill level of an individual but also to find the best method for the student to process information and retain it in long-term memory. Spelling Recovery can be used in two ways: (1) To take specific action after having identified an occasional error made by a particular student, or a common error made by several students in a class; (2) To prioritise learning outcomes and to select appropriate actions helping students with pronounced, multiple spelling problems, once an analysis of their spelling has been made. Recommendations for follow-up and program planning are provided, as are photocopy master sheets for error-analysis and analysis-to-action forms.